EFFECT OF DIFFERENT LEVELS OF PROPOLIS ON SOME PRODUCTIVE TRAITS OF AWASSI EWES - H. N. Abood, H. N. Abood; H. K. Al-Waith , H. K. Al-Waith; S. M. Al-Jubori, S. M. Al-Jubori (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was conducted to investigate the influence of different levels of propolis on the productive traits of Awassi ewes. Twenty-five ewes with similar weights and ages were used and divided into five groups, with five ewes per treatment. Propolis was administered to the ewes daily for a month premating and a month before the expected birth. The groups included: Control group without adding propolis; 5, 10,15 & 20 g of propolis/ewe/day Dosed to T1, T2, T3 & T4 were closed respectively. The experiment continued until the end of lactation season for these ewes. The T3 treatment exhibited higher (P≤0.01) ewe's weight at mating than other groups, greater (P≤0.05) weight at pregnancy than T1 and T4 treatments, and higher (P≤0.05) weight was observed at birth than the T1 and T2 treatments was observed. The T3 and T4 were significantly superior (P≤0.05) in the daily milk yield (DMY) over the control for the 1st  and 2nd productive months. Moreover, T3 exhibited higher (P≤0.05) DMY than T4 and the control in the 3rd productive month. Higher (P≤0.05) milk fat percentage was noticed for T4 than other groups and in the 2nd productive month, whereas T4 was higher (P≤0.01) than with other groups in the percentage of lactose for the 2nd productive month. Higher (P≤0.01) milk protein percentage was observed in T4 treatment over thanT2, T1, and C groups. In conclusion, different levels of propolis affected positively the production performance of Awassi ewes.